Reading performance in school going children with visual function anomalies - Kadir, Syeed Mehbub Ul; Sarkhel, Sunanda; Chakraborty, Sayantan; Maurya, Rajendra Prakash; Akter, Nilufa; Masihuzzaman; Bhardwaj, Gaurav Kumar; Khatun, Mastura (IP International Journal of Ocular Oncology and Oculoplasty, 2024)
To compare reading performance in children with and without visual function anomalies. This cross-sectional study was carried out from May 2021 to April 2022 in a tertiary eye hospital of Bangladesh. This study included patients with 6-15 years of age who visited at Vision Therapy clinic. CISS-score was used to identify the asthenopia complaints and reading difficulties while having a normal vision and normal retinal function only selected for recruitment. Reading error, accuracy and reading speed were assessed with an N-notation chart with an N6 target size and the time taken to complete the task was recorded with a stopwatch. Both univariate and bivariate tables are used for analysis. Statistics analysis was performed accordingly, and the level of significance used was at 0.05. Out of 200 subjects, 46.5% boys and 53.5% girls. Of the total, 15.5% had NVF. The mean age of the participants was 12.04 (±2.44) years. Children with AVF had a higher number of reading errors and non-significant negative correlation (AVF=7.64 (±5.19); NVF 6.55 (±3.67); (r = -1.00, p=0.157). Lower Reading accuracy was noted in AVF as correlated to NVF and non-significant negative correlation (AVF=86.11 (±14.84); NVF=86.43 (±13.12); (r= -0.008, p=0.912). Similarly, lower reading speed was noted in AVF as correlated to NVF and non-significant negative correlation (AVF=79.47 (±39.20) wpm; NVF=84.51±36.84 wpm; (r= -0.047, p=0.507). A statistically significant difference was seen between AVF and NVF (p=0.001 at a 95% Confidence Interval of the differences). Children in the 1 to 5 grades presented a higher risk of reading impairment than the 6 to 10grades. Higher reading speed (112±20.69wpm) was noted in 10 grade. In this study, it was observed that poor reading performance is linked to abnormal visual function in school-aged children, but visual function and reading performance are not positively related.